2019
DOI: 10.1002/jwmg.21722
|View full text |Cite
|
Sign up to set email alerts
|

Woodpecker nest survival, density, and a pine beetle outbreak

Abstract: Mountain pine beetle (Dendroctonus ponderosae) outbreaks in western North American coniferous forests are increasing in size and severity. An understanding of wildlife population responses to pine beetle outbreaks is needed to inform habitat conservation strategies. We monitored 355 nests of 5 woodpecker species during 2 sampling periods, before (2003–2006) and after (2009–2014) the peak of a pine beetle outbreak in dry mixed conifer forest of Montana, USA. Three of 5 woodpecker species represented the beetle‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Information on other factors, including nest density, nest success, fecundity, and survival, is necessary to determine whether species experienced greater fitness during the mountain pine beetle epidemic (Saab et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Information on other factors, including nest density, nest success, fecundity, and survival, is necessary to determine whether species experienced greater fitness during the mountain pine beetle epidemic (Saab et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Saab et al. () found that an eventual decline in the pulse of mountain pine beetles may result in decreases of nest densities for woodpeckers several years after the peak of a beetle outbreak. In addition, dramatic changes in understory growth, downed wood, and canopy cover in the years following the epidemic (Stone and Wolfe , Page and Jenkins , Jenkins et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insect populations are directly influenced by climate because temperature determines rate of larval development, as well as survival and reproduction of adults (Brown, Gillooly, Allen, Savage, & West, 2004; Chuine & Régnière, 2017). Because many birds, especially woodpeckers, respond positively to outbreaks of insects (Edworthy, Drever, & Martin, 2011; Morris, Cheshire, Miller, & Mott, 1958; Norris, Drever, & Martin, 2013; Saab, Latif, Dresser, & Dudley, 2019), changes in climate may alter the diet of these species.…”
Section: Introductionmentioning
confidence: 99%